Disentangling public perceptions to pave the way for pollinator-friendly roadsides - Warner, Laura A.; Gusto, Cody; Pasula, Sravani; Daniels, Jaret; Mattox, Anissa; Honeycutt, Sydney; Telg, Ricky; Lindsey, Angie (Frontiers in Conservation Science, 2025)
IntroductionRapid urbanization and land use changes have resulted in extensive road coverage, making roadsides increasingly important as critical landscapes that can support biodiversity. Pollinator-friendly roadsides offer ecological benefits, but public support is essential for their successful implementation. Despite this, adequate audience analyses to inform impactful public initiatives benefiting pollinators have not been conducted. This research study aimed to document public knowledge, perceptions, concerns, and information-seeking preferences regarding pollinator-friendly roadsides to guide future communication campaigns.MethodsWe conducted an initial, descriptive audience analysis using quota sampling to survey 1,011 Floridians. The survey measured four key areas: (1) knowledge, (2) perceptions, (3) concerns, and (4) preferred communication channels related to pollinator-friendly roadsides. Descriptive statistics were used to quantify the findings.ResultsRespondents demonstrated relatively high perceived and actual knowledge of pollinator-friendly roadsides. Perceptions varied, with both positive and negative views of pollinator-friendly roadsides expressed. Ecological and environmental benefits were ranked as the most important characteristics, while safety concerns and increased expenses emerged as the most significant barriers. Preferred communication strategies included immersive experiences such as demonstration gardens at rest stops and road signage. Social media, particularly YouTube, was identified as the favored digital platform for learning about pollinator-friendly roadsides.DiscussionFindings suggest that educational communications should emphasize ecological benefits while addressing safety and cost concerns and correcting misperceptions. Immersive roadside experiences combined with digital content can enhance public engagement. Future research should include message testing and apply behavioral theory to identify strategies for increasing public support for pollinator-friendly roadsides. Significant opportunities remain to conduct message testing and behavioral theory-based research to uncover ways to increase public support for pollinator-friendly roadsides.